A Morris Semiotic Perspective on the Characteristics and Cultural Significance of Traditional Guangdong Furniture Patterns - Yi, Xi qiong; Yong , Yuan; Abas, Imelda Hermilinda (Journal of Ecohumanism, 2024)
Based on Morris's semiotic theory, this paper systematically analyzes the symbolic features of traditional Guangdong furniture patterns and their cultural symbolism from the three dimensions of semiotics (syntax, semantics, and pragmatics). The study focuses on typical patterns such as dragon and phoenix, pine and crane, plum, orchid, bamboo and chrysanthemum in Guangdong traditional furniture, and explores their historical origins, social functions, and close links with Confucianism, family concepts, and social hierarchies in the context of Lingnan culture. By analyzing these symbols, the paper reveals their special symbolic meanings in different social classes and ritual cultures, as well as how they convey the values and lifestyles of the Guangdong region through visual forms. The study further explores the potential application of these traditional symbols in modern design, especially through simplification and abstraction, combining traditional cultural symbols with modern design concepts, materials and techniques to realize the fusion of cultural heritage and innovative design. This paper provides a new theoretical framework for the study of the patterns of traditional furniture in Guangdong, and practical suggestions for modern designers on how to effectively inherit and innovate the cultural heritage symbols, and to promote the synergistic development of cultural heritage preservation and design industry.